‘AIMing’ for the Target: How has Policy on Inclusion Evolved since the 1990’s in Ireland - Stembridge, Eva (My University, 2019)
This article provides an overview of how inclusion policy for children with additional needs (AN) in Early Childhood Care and Education (ECCE) has evolved in Ireland since the 1990’s. The motivation for this study is the introduction of a new and unique inclusion policy for ECCE in Ireland, called the Access and Inclusion Model (AIM). The AIM is accessible to all pre-school children in Ireland and is paving the way for EYT in partnership with parents in delivering an inclusive early years education experience to children with AN. It is therefore timely, to trace the history of educational inclusion in Ireland.
Journal Article
Keywords: Research Subject Categories::SOCIAL SCIENCES; Early Childhood Education; Policy; Inclusion; Special Education; STER